Relationship Of Mother's Knowledge Level With Immunization In Baby 0-12 Months At Mompangjae Puskesmas, Panyabungan Utara District, Mandailing Regency Year 2022 - Widya putri Siregar (Science Midwifery, 2022)
Immunization is an effort to increase individual immunity to avoid certain diseases. Immunizations that must be given to infants are Hepatitis B, polio, BCG, DPT, measles. Complete basic immunization coverage in Indonesia in 2019 is 71.98%. The purpose of this study was to analyze the relationship between mother's level of knowledge and basic immunization for infants 0-12 months in the Mompang Jae Public Health Center, Panyabungan Utara District, Mandailing Natal Regency. This research is an analytic survey with a cross sectional approach. The sampling method in this study was to use a total sampling technique, that is, all the population was sampled as many as 35 people. The research instrument used primary data (questionnaire) consisting of 20 questions. The data processing technique starts from editing, coding and tabulating, then tested by Chi-Squer test. The results of this study indicate that immunization was given to 35 cases, the majority of which were moderately knowledgeable as many as 14 people (40.0%) and the minority of knowledge was less than 9 people (25.7%). The results of the Chi-Square test obtained p-value = 0.001 <0.05 then Ha is accepted and Ho is rejected which means there is a relationship between Mother's Knowledge Level and Immunization for Babies 0-12 Months in the Working Area of ​​Mompang Jae Health Center, North Panyabungan District, Mandailing Natal Regency. 2022. As a suggestion to research sites, it is hoped that it can motivate cadres and health workers to be more active in providing counseling about the importance of immunization for infants to prevent disease.